Vitiligo: Unmet Need, Management and Treatment Guidelines - Marzano, Angelo Valerio; Alberti-Violetti, Silvia; Maronese, Carlo Alberto; Avallone, Gianluca; Jommi, Claudio (Dermatology Practical & Conceptual, 2023)
Vitiligo is a chronic depigmenting disorder characterized by characteristic, non-scaly, chalky-white skin macules and patches, due to the loss of skin pigment. Its exact pathogenesis is still not fully understood but it seems to be an autoimmune disease where the combination of genetic, environmental, and immune factors contributes to the destruction of melanocytes in the epidermis. Vitiligo is classified into different types based on its clinical characteristics and distribution patterns. The two main forms of vitiligo are non-segmental vitiligo (NSV) and segmental vitiligo (SV). NSV is the predominant form, characterized by symmetrical skin patches, that tend to evolve over time. In contrast, SV has unilateral or band-shaped lesions that progress rapidly but often stabilize early.Herein, current unmet needs in terms of psychosocial consequences and relative lack of valid therapeutic approaches are critically analyzed and put in perspective in the Italian prescribing scenario. Finally, available management guidelines are illustrated and briefly compared, to provide context for upcoming treatment options.